On a fixed point theorem by totik (2009)
In this paper we prove a common fixed point theorem (see Theorem 3.1) in metric spaces for two self-mappings satisfying a general implicit relation involving the diameter of nite sets, without requiring continuity. This theorem may be considered as a generalization of a result by Totik (1983). Also, it unies and generalizes some other results obtained by Fisher (1977), Akkouchi (2001) and Nova (1997).